Potenciál přínosu PCR-HRMA a MALDI-TOF spektrometrie v identifikaci a typizaci bakteriálních patogenů - posouzení na modelu CHOPN, bronchiektázií a cystické fibrózy - Raclavský, Vladislav (2016)
The project consists in a conclusive prospective study of performance of MALDI-TOF spectrometry and High Resolution Melting Analysis of PCR-products (PCR-HRMA) in species identification, and MALDI-TOF and McRAPD in strain typing, compared to reference techniques (16S rDNA sequencing and MLST). For species identification purposes, a commercial MALDI-TOF approach and a published PCR-HRMA approach will be tested. For typing, MALDI-TOF and McRAPD will be tested in Haemophilus influenzae strains. This testing will be performed on bacterial isolates recovered from sputum samples of patients suffering Chronic Obstructive Pulmonary Disease (COPD), Bronchiectasis (BE), and Cystic Fibrosis (CF). Accuracy and reproducibility will be determined for identification techniques and power of resolution for typing techniques. Based on evaluation of clinical data, the true contributing potential of the techniques to improve clinical management will also be estimated.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: Random Amplified Polymorphic DNA Technique; Pulmonary Disease, Chronic Obstructive; Cystic Fibrosis; chronická obstrukční plicní nemoc; Bronchiectasis; techniky typizace bakterií; spektrometrie hmotnostní - ionizace laserem za účasti matrice; multilokusová sekvenční typizace; cystická fibróza; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; bronchiektazie; Blood-Borne Pathogens; pneumologie a ftizeologie; patogeny v krvi; Multilocus Sequence Typing; technika náhodné amplifikace polymorfní DNA; infekční lékařství; Bacterial Typing Techniques